Therapeutic Effects of Magnesium Biotinate on Propionic Acid-Induced Autistic Features in Rats - Sylla, Sarah; Komorowski, James; Ojalvo, Sara; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Şahin, Kazım (Wiley, 2020)
[Abstract Not Available]
Annual Meeting on Experimental Biology -- APR 04-07, 2020 -- San Diego, CA